Energetics and local order in In-based liquid alloys - Koirala, RP; Singh, BP; Jha, IS; Adhikari, D (BIBECHANA, 2015)
A comparative study has been carried out to understand the concentration dependence of thermodynamic properties such as, free energy of mixing, heat of mixing, entropy of mixing, activity  and microscopic properties, such as concentration fluctuation in long wavelength limit  and Warren-Cowley short range order parameter  of  In-based three liquid alloys (In-Pb , In-Tl and In-Zn) on the basis of self-association model. The analysis reveals that self-association model successfully explains the observed properties of the liquid alloys.  Positive deviation of the thermodynamic properties of the alloys from the Raoultian solution behaviour indicates that the alloys are weakly segregating in nature. The comparative assessment of the interaction energy and the microscopic properties suggests that the degree of segregation is greatest in In-Zn alloy and comparable in In-Pb and In-Tl alloys.BIBECHANA 13 (2016) 60-71